2023
DOI: 10.1039/d3ra04230h
|View full text |Cite
|
Sign up to set email alerts
|

Design, green synthesis, and quorum sensing quenching potential of novel 2-oxo-pyridines containing a thiophene/furan scaffold and targeting a LasR gene on P. aeruginosa

Yousry A. Ammar,
Ahmed Ragab,
M. A. Migahed
et al.

Abstract: New 2-oxo-pyridines containing thiophene/furan scaffold targeting LasR gene on P. aeruginosa using green synthesis approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 83 publications
0
5
0
Order By: Relevance
“…Combining 6-amino-4-(thiophen-2-yl)-2-oxo-pyridine-3,5-dicarbonitrile (18) and 6amino-4-(furan-2-yl)-2-oxo-pyridine-3,5-dicarbonitrile (19) with aromatic aldehydes and ketones, two series of antimicrobial Schiff bases (18a-c and 19a-c) were synthesized under both conventional and green conditions (ceric ammonium nitrate catalysis) [109]. Biological screening revealed significant antimicrobial potential for azomethines, especially on Gram-negatives, surpassing or equalizing references (gentamicin and fluconazole) and biocidal modes of action.…”
Section: N-(3-(-2-(7-chloroquinolin-2-yl)vinylmentioning
confidence: 99%
See 3 more Smart Citations
“…Combining 6-amino-4-(thiophen-2-yl)-2-oxo-pyridine-3,5-dicarbonitrile (18) and 6amino-4-(furan-2-yl)-2-oxo-pyridine-3,5-dicarbonitrile (19) with aromatic aldehydes and ketones, two series of antimicrobial Schiff bases (18a-c and 19a-c) were synthesized under both conventional and green conditions (ceric ammonium nitrate catalysis) [109]. Biological screening revealed significant antimicrobial potential for azomethines, especially on Gram-negatives, surpassing or equalizing references (gentamicin and fluconazole) and biocidal modes of action.…”
Section: N-(3-(-2-(7-chloroquinolin-2-yl)vinylmentioning
confidence: 99%
“…Structure-activity relationships revealed that azomethine is important for activity, which varied according to the substituents in position one (imine groups) and four (furanyl, thiophenyl) on pyridine moiety (Figure 6). Benzylidene and 1,3-dioxo-1,3-dihydro-2H-inden-2-ylidene increased the antibacterial spectrum, with electron-donating groups (hydroxy, ethoxy, bromo) being beneficial for MRSA and E. coli biofilm inhibition [109]. P. aeruginosa uses two QS systems, las and rhl, that rely on transcriptional activators (LasR and RhlR, respectively) and autoinducer molecules (N-3-oxo-dodecanoyl-Lhomoserine lactone, respectively N-butyryl-L-homoserine lactone) [143].…”
Section: N-(3-(-2-(7-chloroquinolin-2-yl)vinylmentioning
confidence: 99%
See 2 more Smart Citations
“…By binding to and interacting with rhlR in the rhl TCS, the autoinducer C4-HSL increases RhlI expression and triggers the controlled synthesis of cytotoxic lectins, rhamnolipids, lasB elastase, and Life 2024, 14, 481 2 of 13 pyocyanin, all of which are essential for virulence and the formation and development of biofilms. The QS systems Las, Rhl, Pqs, and Iqs are interconnected hierarchically [4,5].…”
Section: Introductionmentioning
confidence: 99%